Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Let's solve the system of equations using the substitution method. The system of equations is:
[tex]\[ \begin{aligned} 5x + 4y &= 7 \quad \text{(Equation 1)} \\ y &= 2x + 5 \quad \text{(Equation 2)} \end{aligned} \][/tex]
Step 1: Substitute Equation 2 into Equation 1
From Equation 2, we have:
[tex]\[ y = 2x + 5 \][/tex]
We can substitute this expression for \( y \) into Equation 1:
[tex]\[ 5x + 4(2x + 5) = 7 \][/tex]
Step 2: Simplify and solve for \( x \)
Distribute the \( 4 \) inside the parentheses:
[tex]\[ 5x + 8x + 20 = 7 \][/tex]
Combine the \( x \) terms:
[tex]\[ 13x + 20 = 7 \][/tex]
Subtract 20 from both sides to isolate the \( x \) term:
[tex]\[ 13x = 7 - 20 \][/tex]
Simplify the right side:
[tex]\[ 13x = -13 \][/tex]
Divide both sides by 13:
[tex]\[ x = \frac{-13}{13} \][/tex]
So,
[tex]\[ x = -1 \][/tex]
Step 3: Substitute \( x = -1 \) back into Equation 2 to solve for \( y \)
We use Equation 2 to find the corresponding \( y \) value:
[tex]\[ y = 2(-1) + 5 \][/tex]
Simplify:
[tex]\[ y = -2 + 5 \][/tex]
Therefore,
[tex]\[ y = 3 \][/tex]
Solution
The solution to the system of equations is:
[tex]\[ \begin{array}{l} x = -1 \\ y = 3 \end{array} \][/tex]
So, the point [tex]\((x, y) = (-1, 3)\)[/tex] satisfies both equations in the given system.
[tex]\[ \begin{aligned} 5x + 4y &= 7 \quad \text{(Equation 1)} \\ y &= 2x + 5 \quad \text{(Equation 2)} \end{aligned} \][/tex]
Step 1: Substitute Equation 2 into Equation 1
From Equation 2, we have:
[tex]\[ y = 2x + 5 \][/tex]
We can substitute this expression for \( y \) into Equation 1:
[tex]\[ 5x + 4(2x + 5) = 7 \][/tex]
Step 2: Simplify and solve for \( x \)
Distribute the \( 4 \) inside the parentheses:
[tex]\[ 5x + 8x + 20 = 7 \][/tex]
Combine the \( x \) terms:
[tex]\[ 13x + 20 = 7 \][/tex]
Subtract 20 from both sides to isolate the \( x \) term:
[tex]\[ 13x = 7 - 20 \][/tex]
Simplify the right side:
[tex]\[ 13x = -13 \][/tex]
Divide both sides by 13:
[tex]\[ x = \frac{-13}{13} \][/tex]
So,
[tex]\[ x = -1 \][/tex]
Step 3: Substitute \( x = -1 \) back into Equation 2 to solve for \( y \)
We use Equation 2 to find the corresponding \( y \) value:
[tex]\[ y = 2(-1) + 5 \][/tex]
Simplify:
[tex]\[ y = -2 + 5 \][/tex]
Therefore,
[tex]\[ y = 3 \][/tex]
Solution
The solution to the system of equations is:
[tex]\[ \begin{array}{l} x = -1 \\ y = 3 \end{array} \][/tex]
So, the point [tex]\((x, y) = (-1, 3)\)[/tex] satisfies both equations in the given system.
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.